Post-translational coordination of chlorophyll biosynthesis and breakdown by BCMs maintains chlorophyll homeostasis during leaf development - Peng Wang (Nature Portfolio, 2020)
Plants regulate chlorophyll levels to optimise photosynthesis. Here Wang et al. describe two paralogous thylakoid proteins, BCM1 and BCM2, which stimulate chlorophyll biosynthesis and attenuate chlorophyll degradation respectively through interaction with the Mg-chelatase-stimulating factor GUN4 and Mg-dechelatase isoform SGR1.